Intellectual Abilities of High-End Handball Players of Different Playing Roles - Evheny Strialenko; Ihor Zhosan; Oleh Shalar (Lesya Ukrainka Volyn National University, 2018)
The article presents the results of the study of the intellectual abilities of high-end handball players of various gaming roles. It was revealed that the playing players of the Dniproanka team (Kherson) had a high level of intellectual potential (113,3 points), goalkeepers - a level lower (80,3 points). The level of intellectual potential of players in other game roles did not differ significantly and was on average 107 points. By the same method, the goalkeepers of Lviv's Galichanka (98,5 points) scored less points, linear players showed a score of 110,5 points. The intellectual potential of the welterweight, angular and playing players was high and averaged 120,2 points. It is established that the angular players of handball team «Dniproanka» had the highest IQ (according to Eysenck's method) among players of other gaming roles, which was 108,4 points. In the team «Galichanka» the best ratio among the playing players (114 points), in contrast to them at the goalkeepers, he was 103,5 points. Players of other game roles on average scored 107,5 points. The higher level of intellectual abilities of playing players in both teams can be explained by the peculiarities of the playing role, which are the «conductors» of the game.